Management of melasma in adult women (Research, Society and Development, 2021)
Objective: To describe the treatments available for melasma in adult women. Methodology: This is an integrative review about the treatments available for adult women with melasma, through searches in the following databases: Medical Literature Analysis and Retrieval System (MEDLINE/PubMed), Scientific Electronic Library Online (SciELO) and Literature Latin American and Caribbean Health Sciences (LILACS). Altogether, 23 articles were included in this review. Results: After analyzing the treatments used in the selected works, five categories of treatments were identified, namely: use of tranexamic acid, microneedling treatments, laser treatments, treatments with plant extracts and other treatments. Conclusion: This article considered that when comparing topical treatment with tranexamic acid and hydroquinone the results are similar, however the second option has more adverse effects. In patients with frequent relapses, the association of microneedling contributes to an increase in the effectiveness of tranexamic acid, with laser therapy being another management option in these cases. In addition, formulations containing plant extracts show improvement in hyperchromic spots, as well as other treatments.